Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2018)
Photorefractive keratectomy with intraoperative mitomycin-C application Lee DH, Cluing HS, Jeon YC, Boo SD, Yoon YD, Kim JG J Cataract Refract Surg. 2005; 31: 2293-8. Clinical results of the blue-light filtering AcrySof Natural foldable acrylic intraocular lens Marshall J, Cionni RJ, Davison J, Ernest P, Lehmann R, Maxwell A, Solomon K J Cataract Refract Surg 2005; 31: 2319-23. Evidence for the use of nutritional supplements and herbal medicines in common eye diseases West AL, Oren GA, Morol SE Am J Ophthalmol 2006; 141: 157-66. Retinopathy of prematurity: the life of a lifetime disease Tasman W, Patz A, McNamara JA, Kaiser RS, Trese MT, Smith BT Am J Ophthalmol 2006; 141: 167-74. Amblyopia: Diagnostic and therapeutic options Carolyn WU, Hunter DG Am J Ophthalmol 2006; 141: 175-84. Long-term changes in corneal surface configuration after penetrating keratoplasty Hayashi K, Hayashi H Am J Ophthalmol 2006; 141: 241-47. Move Stem Cells From the Mouth to the Eye Tseng SCG Am J Ophthalmol 2006: 141: 356-7.